WATER QUALITY OF THE KAHAYAN RIVER, PALANGKA RAYA, CENTRAL KALIMANTAN: Kualitas Air Sungai Kahayan, Palangka Raya, Kalimantan Tengah - Abdurrahman; Ray Kentkhute; Lutfiah Nur Hasinah (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
The Kahayan River is a river that flows in the middle of the city of Palangka Raya, where all forms of human activity exist along the Kahayan river, both for toilets, industry and other tourism activities. This of course will affect the physical and chemical quality of the waters. Coupled with the rise of illegal miners along the Kahayan River, it has damaged the river's ecosystem. Analysis of water quality by comparing water quality to the quality standard thresholds set by the government (PP No.22/2021). Based on the research results, the water quality of the Kahayan River has met the quality standards for several parameters. Among them are physical parameters, namely temperature ranging from 31.7 oC – 32.7 oC, current speed of 0.3 – 0.5 m/sec, TSS 8-14 mg/L, TDS has a range of 345 mg/L – 368 mg/L . while the chemical parameters that have met quality standards include, pH ranges from 7.3 - 7.2 m/L, DO ranges from 7.2 mg/L - 7.5 mg/L. Meanwhile, the water quality of the Kahayan River has exceeded the quality standard for several parameters including physical parameters, namely Brightness 25-31cm, BOD 4.24 mg/L - 4.48 mg/L and COD in the range 13.75 mg/L – 22.74 mg/L.